Editorial: Navigating modern economic landscapes: Digital Sharia trends, behavioral insights, and inclusive growth - Hendryadi, Hendryadi (SERAMBI: Jurnal Ekonomi Manajemen dan Bisnis Islam, 2025)
This editorial introduces a compelling collection of research that explores the dynamic intersections of digital transformation, Islamic behavioral finance, and sustainable economic development. The studies in this issue examine how digital platforms—from social media to QRIS payment systems—are reshaping investment behaviors, consumer patterns, and financial inclusion within Sharia-compliant frameworks. Key themes include the influence of herding behavior in Islamic capital markets, the role of halal consumption on physical well-being, and the impact of foreign and Sharia investment on Indonesia's economic trajectory. Additionally, this issue addresses critical issues such as inflationary pressures on welfare, patient satisfaction in healthcare services, and user perceptions of Sharia mobile banking. Collectively, these works highlight the evolving role of Islamic principles in guiding ethical and rational economic behavior in increasingly digital and globalized contexts.